Analysis of TikTok Live Streaming Programs as a Promotional Medium for Thrift Fashion Businesses - Nazwa Reza Asevi; Septian Wahyudi (Escalate : Economics and Business Journal, 2026)
This research analyzes TikTok live streaming as a promotional medium for thrifting fashion businesses. The background addresses how interactive live streaming features enhance pre-owned apparel sales while presenting competitive and technical challenges alongside spontaneous consumer behavior. The study aims to examine TikTok live streaming utilization in thrifting business promotion, focusing on feature deployment, encountered challenges, and applied marketing strategies. The methodology employs qualitative descriptive case study design through semi-structured interviews with Windyy_Shop proprietors. Purposive sampling selected business operators and hosts demonstrating expertise in live streaming operations. Data collection instruments included in-depth interviews and operational observation. Thematic analysis employing Braun and Clarke's framework provided qualitative interpretation. Results demonstrate that live streaming reduces information asymmetries, facilitates real-time consumer engagement, and significantly accelerates purchasing decisions. Eight operational mechanisms emerged, including interactive product visualization, competency-based host selection, and algorithmic platform optimization. Findings reveal substantial sales conversion rate increases, elevated customer loyalty, and expanded brand awareness despite technical infrastructure constraints and competitive saturation. The research concludes that live streaming functions as a multidimensional promotional mechanism generating meaningful business performance enhancement through comprehensive psychological consumer engagement across emotional, social, and interactive dimensions.